Can Learning Agility Predict Students’ Academic Burnout During Distance Learning - Putri Adinda Novianti; Whisnu Yudiana; Shally Novita (Journal of Educational, Health and Community Psychology, 2023)
Various new academic challenges faced by students during the distance learning period lead to vulnerability in academic burnout. This condition requires them to become agile learners to be able to face various challenges in new learning situations. This study aims to determine the role of learning agility on students’ academic burnout during distance learning. The online survey provided quantitative data from 210 students taking distance learning. The Learning Agility Scale and the Maslach Burnout Inventory-Student Survey (MBI-SS) were used to measure student learning agility and academic burnout, respectively. The results show that learning agility is a significant predictor of academic burnout, so the higher the learning agility, the lower the level of academic burnout. Furthermore, the difference in the length of study did not affect learning agility role on students’ academic burnout. The implication and limitation of this study are discussed in this article.